2023
DOI: 10.3389/fpls.2023.1324820
|View full text |Cite
|
Sign up to set email alerts
|

An appropriate ammonium: nitrate ratio promotes the growth of centipedegrass: insight from physiological and micromorphological analyses

Dong-Li Hao,
Jin-Yan Zhou,
Ling Li
et al.

Abstract: Reasonable nitrogen fertilizer application is an important strategy to maintain optimal growth of grasslands, thereby enabling them to better fulfil their ecological functions while reducing environmental pollution caused by high nitrogen fertilizer production and application. Optimizing the ammonium (NH4+):nitrate (NO3-) ratio is a common approach for growth promotion in crops and vegetables, but research on this topic in grass plants has not received sufficient attention. Centipedegrass, which is widely used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Yang et al [56] found such dependencies in the early stages of wheat growth. For most species, fertilisers had the greatest effect on the growth and development of plants in which the NH 4 + :NO 3 − ratio was 50:50 [57]. The application of the higher nitrogen dose probably caused physiological stress at the beginning of spring wheat vegetation in our own research.…”
Section: Discussionmentioning
confidence: 52%
“…Yang et al [56] found such dependencies in the early stages of wheat growth. For most species, fertilisers had the greatest effect on the growth and development of plants in which the NH 4 + :NO 3 − ratio was 50:50 [57]. The application of the higher nitrogen dose probably caused physiological stress at the beginning of spring wheat vegetation in our own research.…”
Section: Discussionmentioning
confidence: 52%
“…In view of the above, it is extremely important to adjust the doses of fertilizers to the fertilization needs of particular plant species while taking into account the direct and indirect effects of fertilizers on the course of physiological and biochemical processes in plants. Fertilization with ammonium nitrogen, nitrate nitrogen and potassium in appropriate proportions has a particular influence on the uptake of nitrogen by plants and the synthesis of organic nitrogen compounds [48,49]. The content of nitrogen in wheat is strictly correlated with the dose of N fertilizer [50,51] and the time of its application [35].…”
Section: Discussionmentioning
confidence: 99%
“…According to Hao et al [48], the application of N fertilizers containing both nitrate nitrogen and ammonium nitrogen can produce higher crop yields than those containing only one of these forms of nitrogen. An example of the former is urea and ammonium nitrate, whose positive effect on plant growth, development and chemical composition was observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation